(untitled) (Revista Científica Estelí, 2015)
This article consists of quality control systems carried out in tobacco factories in the city of Estelí, in northern Nicaragua controlling the environment in terms of manufacturing of cigars, showing the efficiency and effectiveness of workers in this area which has brought up the Estelí economy. The complete article encompasses real and reliable technical information focused on quality management systems, for the manufacturing of cigars in tobacco companies, in order to provide a basic, useful and simple document. It is necessary to note the different checkpoints that may occur in the production processes, which are made in pure manufacturing plants providing guidelines for the continuous improvement of the quality standards necessary to satisfy the customer. Keywords: Quality, continuous improvement, productivity, savings